Konseling kelompok untuk menurunkan stres selama sekolah daring - Yana Damayanti (Universitas Muhammadiyah Malang, 2022)
During the pandemic, learning at school is delivered by online. Online schools make many students experience stress due to the burden of the lessons. During this pandemic the learning methods provided by schools are more difficult to understand. The purpose of this case study is to reduce the symptoms of stress in students by using group counseling. The assessment method uses interviews, observation, and the Educational Stress Scale for Adolescents (ESSA). The subjects in this case were 5 teenagers aged 13 to 14 years old. The subjects were junior high school students in class VII and class VIII. All subjects live together in a boarding school in Malang. Before the intervention, the stress level of the subjects was in the high category. After the intervention with group counseling decreased to a moderate level.